IMPLEMENTASI PERMENDIKNAS RI NO 25 TAHUN 200 TENTANG STANDAR TENAGA PERPUSTAKAAN SEKOLAH/MADRASAH DI SMA NEGERI I PEKANBARU - Yuhelmi, Yuhelmi; Rismayeti, Rismayeti (Jurnal Ilmu Budaya, 2016)
This writing aims to describe weather Permendiknas RI No 25 in 2008 about the standard of school librarian has been implemented in SMA 1 Pekanbaru as the oldest high school in Pekanbaru besides to find out what factor/s contribute to hinder the implementation of that Permendiknas in order the librarians are able to fulfill the criteria or the standard of Permendiknas RI No 25 in 2008.